A synopsis of the British flora arranged according to the natural orders - Lindley, John 1799-1865 (Cambridge University Press, 2015)
The botanist and horticulturalist John Lindley (1799-1865) worked for Sir Joseph Banks, and was later instrumental in saving the Royal Horticultural Society from financial disaster. He was a prolific author of works for gardening practitioners but also for a non-specialist readership, and many of his books have been reissued in this series. This 1829 work is a classification of British plants using the 'natural' system of the French botanist Antoine Laurent de Jussieu, which Lindley firmly supported, believing that the Linnaean system was both inaccurate and had 'almost disappeared from every country but our own'. Lindley describes genera and species in English, but using a uniform, standard vocabulary, and gives the alternative Latin names proposed by taxonomists including Smith, Curtis, Linnaeus, and the Hortus Kewensis. He also offers tables showing the components of each genus, and substantial indexes giving both Latin and English common names of the plants discussed.